Optimizing Mobile-Assisted Inquiry Learning with Interactive Videos to Boost Scientific Explanation and Understanding of Seventh Graders - Autchima Thinnongwaeng; Niwat Srisawasdi; Pawat Chaipidech (Engineering Proceedings)
Interactive videos and digital technology have been recognized by educators as supportive tools for learning science. To assess their impact, we compared seventh-grade students’ abilities to explain scientific phenomena and understand climate change using interactive videos. Eighty-for students from a public secondary school participated in this research. They were divided into two groups, one using KKU iNote (EG1) and the other combining KKU iNote with interactive videos (EG2). Significant differences were observed in the scientific explanation scores between groups, with EG2 outperforming EG1. This suggested that interactive videos boosted students’ competency in explaining scientific concepts. Moreover, both groups showed an improved understanding of climate change in post-learning, indicating the positive impact of inquiry-based learning. In particular, EG2 scored higher in their scientific understanding than EG1. This implied that integrating digital technology, particularly interactive videos, effectively enhanced students’ scientific explanation and understanding during inquiry-based science learning.